Influence of Political Billboard Advertising on Non-Literate Electorates’ Voting Intentions in 2022 Governorship Election - Oladipo Mary Oluwaferanmi (Polit Journal Scientific Journal of Politics, 2026)
Political campaigns are planned endeavours by political parties to win over the public. The purpose of a political billboard campaign is to create awareness, persuade and remind voters of the political party’s programmes and candidates. Since billboard uses large graphics and pictures, they are on the basis of the findings, the study concluded that, though billboard can serve as a reminder to the non-literate electorates. This study thus sought to find out whether billboard adverts influenced the intention to vote among non-literate electorates in Osun State. This work was anchored on political mobilization, rational choice, and agenda-setting theories. Political mobilization theory explains the strategies political parties use to mobilize electorates, rational choice assumes that individuals have preferences out of available choices of alternatives, agenda-setting theory examines how the media influences the importance and salience of various topics in public discourse, on the basis of the attention paid to them. The survey method was used to gather data from 389 Ede respondents from North and South Osun state. Responses were analyzed using descriptive statistics of frequency counts, and the result was presented in percentages and tables. Findings revealed that the non-literates had a pre-determined candidate of choice on the basis that the candidate was from the same area as the respondents. However, findings further revealed that political billboard adverts reinforce the predetermined choice and constantly remind them of the political party/candidate to vote for. This research recommended to political parties since they are focusing on non-literates that there should be the use of clearer pictures and more visible graphics for easy identification of political parties as this may encourage these non-literates to vote for them when they see the billboard.